Self-Handicapping and Self-Esteem Levels of Taekwondo Referees - Yetkin Utku Kamuk (Türk Spor ve Egzersiz Dergisi)
This study investigated the self-handicapping and self-esteem levels of taekwondo referees. The population was consisted of 437 Taekwondo referees which serve as official referees in the Turkish Taekwondo Federation and the study group was consisted of 82 active referees (female=36, male=46). Data were collected by inviting the referees to take part in the study during the Turkish Taekwondo Championships held in different cities. All the necessary written permissions including the ethics approval and permission from the central referee committee were obtained. Hitit University Ethics Committee approved the study. The volunteers were asked to give written consent. Statistical analyses were held by using independent samples t test, one-way ANOVA, Tukey HSD as post-hoc and Pearson’s r. The level of significance was predetermined as .05 for all statistical analyses. To collect data, self-esteem scale by Rosenberg and self handicapping scale by Rhodewalt were used. The scales’ Turkish adaptations were done by Tukuş and Akin, respectively. Statistical analyses revealed that taekwondo referees' self-handicapping scores were high and self esteem scores were moderate. The referees' self-handicapping scores were not significantly different by any variable. A significant difference in self-esteem scores by the place of residence was observed. It is concluded that additional researches should be done to set out the reasons for the high self-handicapping scores of taekwondo referees.